Pelatihan Pemanfaatan Microsoft Power bi untuk Analisis dan Visualisasi Data di kanwil DJB Jawa Barat II - Saripudin Saripudin; Widiastuti Murtiningrum (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
The advancement of information technology has encouraged government institutions to optimize data utilization to support accurate and evidence-based decision making. The Regional Office of the Directorate General of Taxes (DGT) West Java II requires effective data management and analysis to support performance monitoring and evaluation. This activity aims to enhance employees’ competencies in processing, analyzing, and visualizing tax data using Microsoft Power BI, as well as to equip participants with skills in developing interactive dashboards as decision-support tools. The training methodology consisted of Business Intelligence concept delivery, hands-on data processing practice, data modeling, and dashboard development based on case studies. The results indicate an improvement in participants’ understanding and technical skills in utilizing Power BI for tax data analysis. The resulting dashboards are able to present information in a concise, interactive, and easily understandable manner, thereby supporting data-driven monitoring, evaluation, and decision making. This training contributes to the implementation of digital transformation and the strengthening of an analytical culture within the DGT Regional Office of West Java II.